'This is real now because it's a piece of paper': texts, disability, and LGBTQ parents. Issue 5 (27th May 2016) - Gibson, Margaret F.
Abstract: What role do texts play in LGBTQ (lesbian, gay, bisexual, transgender, and queer) parents' experiences of disability service systems? In interviews with 15 LGBTQ parents of disabled children in Toronto, Canada, participants selected documents to be used as a focus for discussion. Parents considered how LGBTQ identity and other intersectional identities influenced their experiences of institutional texts including adoption certificates, intake forms, and assessments. Findings suggest that documentation practices can operate as forms of systemic gatekeeping. LGBTQ identity was sometimes very significant in parents' accounts, and sometimes less central than other aspects of their families' identities and experiences.